Exploring Endeavour of Health Facilitators Reinforce Public Consciousness on Stunting Reduction - Setiawan, Koesworo; Agustin, Sri Ayu; Juantara, Muhammad Aziz; Hakim, Muhammad Fadly (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Health facilitators (IHT cadres/posyandu and village midwives) play a strategic role in preventing stunting. This study aims to uncover how health facilitators strengthen family awareness using Aristotle's persuasive analysis. Primary data were collected using in-depth interview techniques with informants determined by the purposive sampling method. Secondary data were collected by observation techniques during the interaction process between health facilitators and target groups and literature studies. Next, the data was encoded and analysed with Aristotle's three persuasive concepts: ethos, pathos, and logos. The results showed that health facilitators interacted directly with the target group through two important moments: during health checks at posyandu, and sweeping people's homes. The facilitator's knowledge is sourced from MCH books and other valid references. In conclusion, the facilitator applies interpersonal communication (counseling) to reinforce consciousness of the target group, which is reinforced by Aristotle's persuasion techniques: ethos, pathos, and logos. Through direct interaction, they convince and change family views, beliefs, and behaviours to comply with stunting guidelines. Facilitators promoted three key messages in strengthening consciousness: maternal and child health, healthy behaviours and lifestyles, and environmental health.